Immunomodulatory Effects of Diterpenes and Their Derivatives Through NLRP3 Inflammasome Pathway: A Review - Islam, Muhammad Torequl; Bardaweel, Sanaa K.; Mubarak, Mohammad S.; Koch, Wojciech; Gaweł-Beben, Katarzyna; Antosiewicz, Beata; Sharifi-Rad, Javad (Frontiers in Immunology, 2020)
Nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing protein (NLRP) inflammasomes are involved in the molecular pathogenesis of many diseases and disorders. Among NLRPs, the NLRP3 (in humans encoded by the NLRP3 gene) is expressed predominantly in macrophages as a component of the inflammasome and is associated with many diseases, including gout, type 2 diabetes, multiple sclerosis, atherosclerosis, and neurological diseases and disorders. Diterpenes containing repeated isoprenoid units in their structure are a member of some essential oils that possess diverse biological activities and are becoming a landmark in the field of drug discovery and development. This review sketches a current scenario of diterpenes or their derivatives acting through NLRPs, especially NLRP3-associated pathways with anti-inflammatory effects. For this, a literature survey on the subject has been undertaken using a number of known databases with specific keywords. Findings from the aforementioned databases suggest that diterpenes and their derivatives can exert anti-inflammatory effects via NLRPs-related pathways. Andrographolide, triptolide, kaurenoic acid, carnosic acid, oridonin, teuvincenone F, and some derivatives of tanshinone IIA and phorbol have been found to act through NLRP3 inflammasome pathways. In conclusion, diterpenes and their derivatives could be one of the promising compounds for the treatment of NLRP3-mediated inflammatory diseases and disorders.